Hubungan penyakit jantung bawaan pada anak dengan status pendidikan orang tua - Munaiseche, Kimberly; Munayang, Herdy; Kaunang, Erling D. (e-CliniC, 2016)
Abstract: Congenital heart disease (CHD) has an incidence of 30% of all congenital abnormalities. The incidences of CHDs in developed countries and developing countries range from 6-10 cases per 1000 live births, with an average of 8 per 1,000 live births. Education and knowledge of parents play important roles in the treatment of CHD. This study was aimed to determine the relationship between CHD in children and the educational status of parents. This was an analytical observational study with a cross sectional design. Subjects were all children admitted to the Pediatrics Department Prof. Dr. R. D. Kandou Manado in 2014-2015 due to heart diseases. Data consisted of sex, age, and the last education of the parents. Data were analyzed by using the Chi-Square test. The results showed that there were 100 children with heart diseases consisted of 53 males and 47 females. There were 38 males (52.8%) with positive CHD and the highest percentage of positive CHD was at 7-12 years as many as 17 children (60.7%). Based on education level, most of the children’s fathers were senior high school (42.9%) as well as the children’s mother (53.6%). The Chi-Square showed p= 0.776 and p= 0.532 for the relationships between the fathers’ as well as the mothers’ education levels and congenital heart disease in children. Conclusion: There was no significant relationship between parents’ educational level and congenital heart disease in children.Keywords: congenital heart disease, education. Abstrak: Penyakit jantung bawaan (PJB) merupakan kelainan bawaan yang sering dijumpai, dengan angka kejadian 30% dari seluruh kelainan bawaan. Insiden PJB dinegara maju maupun negara berkembang berkisar 6-10 kasus per 1000 kelahiran hidup, dengan rata-rata 8 per 1000 kelahiran hidup. Pendidikan, pengetahuan, dan pekerjaan orang tua berperan penting dalam penanganan PJB. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara PJB pada anak dengan status pendidikan orang tua. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Subjek penelitian ialah semua anak dengan penyakit jantung yang dirawat di Instalasi Rawat Inap di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado tahun 2014-2015. Data diambil dari Bagian Rekam Medik berupa jenis kelamin anak, usia anak, serta pendidikan terakhir ayah dan ibu. Analisis data dilakukan dengan uji Chi-Square. Hasil penelitian mendapatkan jumlah subjek penelitian sebanyak 100 anak terdiri dari 53 anak laki-laki dan 47 anak perempuan. Berdasarkan jenis kelamin yang terbanyak positif PJB ialah laki-laki sebanyak 38 orang (52,8%). Berdasarkan usia yang terbanyak positif PJB ialah 7-12 tahun sebanyak 17 anak (60,7%). Pendidikan terbanyak ialah SLTA yaitu pada ayah 42,9% dan pada ibu sebesar 53,6%. Uji Chi-Square, mendapatkan p = 0,776 dan p = 0,532 untuk hubungan tingkat pendidikan ayah dan ibu dengan PJB. Simpulan: Tidak terdapat hubungan bermakna antara tingkat pendidikan orang tua dengan penyakit jantung bawaan pada anak. Kata kunci: penyakit jantung bawaan, pendidikan